2021
DOI: 10.7759/cureus.12836
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Intravenous Immunoglobulins in Management of Toxic Shock Syndrome: An Updated Literature Review

Abstract: Toxic shock syndrome (TSS) is an uncommon complication of infection caused by streptococci and staphylococci. It is associated with a high mortality rate. When evaluating patients with shock symptoms from skin or soft tissue sources, a high index of suspicion for TSS must be maintained. Prompt diagnosis and integrative management with surgical intervention, antibiotics, hemodynamic stabilization, and adjuvants like intravenous immunoglobulins improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Clindamycin is a frequent choice given its action of ribosome and the consequent ability to inhibit protein synthesis, therefore limiting the production of GAS toxins [ 22 ]. Similarly, IVIG can neutralize toxin activity [ 23 ]. However, none of the studies that used clindamycin or IVIG were randomized or randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Clindamycin is a frequent choice given its action of ribosome and the consequent ability to inhibit protein synthesis, therefore limiting the production of GAS toxins [ 22 ]. Similarly, IVIG can neutralize toxin activity [ 23 ]. However, none of the studies that used clindamycin or IVIG were randomized or randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Some antibiotics (clindamycin, rifampicin, or linezolid) possess antitoxin effects by reducing exotoxin synthesis which may result in reduction in inflammation and cytokine storm [ 15 ]. IVIG neutralize the superantigens [ 25 , 26 ] and has been shown to reduce mortality in TSS, especially in streptococcal TSS in adults [ 27 , 28 ]. Although definitive evidence for beneficial effects of either IVIG or clindamycin in children with TSS is lacking, they are relatively safe treatments and suggested as adjunctive treatment in children with TSS [ 5 , 15 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 A recent literature review, however, mixing adult and paediatric data, suggested intravenous IG efficacy. 17 Ig M-enriched immunoglobulin (IgGAM) could be an alternative to intravenous IG as it has been reported to improve survival in adult septic shock. 16 18 19 Data on the use of IgGAM in children with TSS are scarce.…”
Section: Original Researchmentioning
confidence: 99%
“…A second RCT that enrolled less than 50% TSS patients reported inconclusive results on mortality or organ failure and physical functioning 16. A recent literature review, however, mixing adult and paediatric data, suggested intravenous IG efficacy 17. Ig M-enriched immunoglobulin (IgGAM) could be an alternative to intravenous IG as it has been reported to improve survival in adult septic shock 16 18 19.…”
Section: Introductionmentioning
confidence: 99%